Composition of Unrecorded Distilled Alcohol (bai jiu) Produced in Small Rural Factories in Central China. (16th December 2016) - Newman, Ian; Qian, Ling; Tamrakar, Niran; Feng, Yonghua; Xu, Ganrong
Abstract : Background: Unrecorded traditional distilled spirits ( bai jiu, 白酒) are made and used throughout rural China for everyday use and special occasions. Nearly every town or village has a distiller to supply the demand. In rural China, distilling bai jiu is legal and regulated lightly or not at all. The World Health Organization estimates that as much as 25% of all alcohol consumed in China is unrecorded alcohol, of which an unknown portion is unrecorded bai jiu . Little is known about the composition of unrecorded Chinese spirits from rural parts of the country. This study focused on white spirits because the high ethanol (EtOH) concentration makes them more likely to contribute to health risks compared to other types of lower alcohol by volume (ABV) Chinese unrecorded alcohol. Methods: Researchers purchased samples of Chinese white spirits from small‐factory distillers in central China. An independent laboratory conducted the analysis. Alcohol strength (ABV) was determined by hydrometer. Gas chromatography was used to determine the concentration of volatile organic compounds: EtOH, methanol, acetaldehyde, ethyl acetate, and higher alcohols. Samples were tested for 3 heavy metals—arsenic, cadmium, and lead. We used the guidelines developed by the Alcohol Measures for Public Health Research Alliance (AMPHORA) of the European Commission to assess risk. Results: ABV ranged from 35.7 to 61.4%, and 58 of the 61 samples exceeded 40% ABV. The concentration of methanol, ethyl acetate, lead, arsenic, and cadmium was below AMPHORA guideline. The sum of higher alcohols exceeded the AMPHORA maximum in just 1 sample. Forty of the 61 samples had acetaldehyde levels beyond the AMPHORA guideline. Conclusions: The unrecorded Chinese alcohols we analyzed had a high EtOH concentration—a public health concern that is also presented by recorded alcohols. The high percentage of samples (65.5%) that had elevated acetaldehyde suggests the need to investigate the causes for this result and the need for steps to reduce acetaldehyde levels. The cumulative long‐term risks of using high EtOH and high acetaldehyde Chinese spirits are heightened by the percentage of people in China who have a genetic trait for impaired acetaldehyde metabolism. Abstract : Samples of unrecorded Chinese white spirits ( bai jiu ) were purchased from small factories in rural China. Bai jiu is traditionally stored in ceramic jars that are stoppered with heavy sandbags covered in cloth. Sellers ladled bai jiu into the researcher's container. Samples were analysed by an independent laboratory. The analysis identified high ethanol concentration and the presence of high levels of acetaldehyde as two possible health risks from this type of traditional Chinese spirits.